PSX-A-7 Late-Breaking: Correlation of mitochondrial membrane potential and rough motility scores in cryopreserved bovine spermatozoa. (8th October 2021) - Clark, Lauren; Waddell, Jolena N; Roper, David; Smith, William B; Runyan, Cheyenne L
Abstract: Spermatozoon motility is an important factor in successful artificial reproductive technologies. Successful reproduction requires properly developed spermatozoa with adequate forward, progressive motility that allows for transport through the female reproductive tract. Motility is driven by production of ATP; however, cryopreservation is known to have damaging effects on spermatozoa. Mitochondria utilize oxidative phosphorylation to synthesize ATP through an electrochemical proton motive force that is composed primarily of mitochondrial membrane potential (Δψm). The mitochondrial membrane potential can be measured using a fluorescent, carbocyanine JC-1 dye (5, 5', 6, 6'-tetrachloro-1, 1', 3, 3'-tetraethylbenzimi-dazolylcarbocyanine iodide). The objective of this study was to examine correlations between the mitochondrial membrane potential and motility score. Cryopreserved semen samples from three bulls were donated to Tarleton State University for research purposes. Samples were thawed, placed under a phase contrast microscope, and analyzed by three individuals with varying levels of training for rough motility. These samples were then prepared with JC-1 dye according to manufacturer's instructions. Two microliters of dye were added to a stock preparation of each sample. Samples were examined on a FACS Calibur flow cytometer at University of Texas Southwestern Core in Dallas, TX. Flow cytometry analysis was performed using FlowJo V10.7. Statistical analysis was performed using SAS v9.4. The Pearson correlation coefficient showed a strong, positive correlation (r = 0.90) between the mitochondrial membrane potential and motility (P = 0.28), thus indicating as the mitochondrial membrane potential increases, so does the rough motility score. These data represent a subset of a population that demonstrates the need of further research on the ability for spermatozoa to produce ATP and the correlation in forward, progressive motility. This research can provide a foundation in which future researchers may develop an assay that allows for testing of mitochondrial membrane potential by producers to select bulls with greater breeding potential.